KARAKTERISTIK ORGANOLEPTIK TEKSTUR STIK IKAN ASAP YANG DICOATING DENGAN PENAMBAHAN MIOFIBRIL DAN KOLAGEN IKAN SITUHUK HITAM (Makaira indica). [Organoleptical Texture Characteristics of Smoked Fish Stick, Coated with Addition of Myofibrils and Coll - Rahael, Kristhina P.; Berhimpon, Siegfried; Mentang, Feny (Jurnal Ilmu dan Teknologi Pangan, 2014)
The use of synthetic packaging caused a big problem of non-degradable waste, therefore the industries started using biodegradable packaging, and recently  research on edible film took attentions of many researches.  Edible film made from biopolymers are expected can provided  certain characteristics as food packaging. This research aims were to study the textural organoleptic characteristics of edible coating made from  collagen and myofibril with the addition of smoke liquid. Edible film made from smoke liquid 0.8%, and then  added collagen and myofibril with concentration of  2, 4, 6, 8, and 10%. The solution were then heated and added sago starch, glycerol, and  bees wax, while hot stirred for 25 minutes.. Furthermore, smoked fish stick was coated using immersion method, and dried for 4 hours.  Coatted fish stick was then fried, and thenfried samples were used as sample for hedonic assessments of  appearance, color, smell, flavor. and texture. The same samples were also prepared  for textural assessment of firmness, elasticity, hardness, and juiciness. The data obtained from the study were analyzed using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at the 0.05 significance level α. The results shown that kind of protein gave a significant effect on the organoleptical characteristics. The best treatment  of edible coating on smoked fish stick was for addition of collagen 6% due to the hedonic value (appearance, color, odor, and texture) and the texture (firmness, elasticity, hardness and juiciness) were more  acceptable by the panelists